Остался голос: проза / Елена Алексеева - Алексеева Елена (Целевая программа "Дети Ижевска", 2005)
Экземпляры: КР (20081014) / Инвентарный номер: 1071698 / Цена: 30.00 / Сис.шифр: Р2 / Авт.знак: А 47 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4